2022
DOI: 10.1155/2022/3252718
|View full text |Cite|
|
Sign up to set email alerts
|

High-Quality Nursing Combined with the Whole-Course Responsibility Nursing Intervention Reduces the Incidence of Complications in Severe Aneurysmal Subarachnoid Hemorrhage

Abstract: Objective. The aim of this study is to study the influence of whole-course responsibility nursing combined with high-quality nursing intervention on the level of life and complications of severe aneurysmal subarachnoid hemorrhage patients with postoperative coma. Methods. From December 2018 to December 2020, 90 severe aneurysmal subarachnoid hemorrhage patients with postoperative coma were selected and were divided into two groups, the experimental group and the control group, with 45 cases in each group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The whole-process case management model provides a more comprehensive medical service compared with the general hospitalization mode. The main highlight of the whole-process case management model is managed participation in the entire treatment course, which can also be regarded as an extension of the hospitalization routine treatment outside the hospital[ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The whole-process case management model provides a more comprehensive medical service compared with the general hospitalization mode. The main highlight of the whole-process case management model is managed participation in the entire treatment course, which can also be regarded as an extension of the hospitalization routine treatment outside the hospital[ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%